The Model of Application of Thai Traditional Medicine in Treating Knee Osteoarthritis Patients with Dhamma Medicine According to Buddhist Guidelines, , Nong Ruea District, Khon Kaen Province: Case Study Wat Srichomchean - Unkaew, Nalinrat; Phrakhru Sudhikhambhirayan; Phramaha Daosayam Vajirapañño (Dhammathas Academic Journal, 2022)
The objectives of this dissertation were: 1) to study the treatment of knee osteoarthritis patients according to Thai traditional medicine; 2) to study the treatment of knee osteoarthritis patients using Dhamma medicine according to the Buddhist guidelines in Nong Ruea District; 3) to propose a model of application of Thai traditional medicine for treating knee osteoarthritis patients with Dhamma medicine according to Buddhist guidelines in Nong Ruea District: Case Study Wat Srichomchean. It is a qualitative research. The reserve area was chosen by purposive sampling in Nong Ruea District, Khonkaen Province. A total of 44 person for Specific Key Informant is a group of patients with osteoarthritis, Primary caregiver/family member of osteoarthritis patient, Thai traditional physicians treating knee osteoarthritis patients, Monks, Community leaders and Village Health Volunteers (VHVs) were collected by in depth interviews and participatory observation. This study was conducted employing qualitative research. The obtained data were interpreted by descriptive analysis. The research results revealed as follows: 1. Thai traditional medicine uses Thai massage therapy, herbal compression, herbal wrap, and exercises to manage knee joints with yoga. This helps reduce knee pain. 2. Most of the patients with osteoarthritis are elderly. Therefore, a Dhamma talk activity was created on Buddhist holy day to apply Thai traditional medicine to treat osteoarthritis patients with Dhamma medicine according to Buddhist guidelines at Sri Chom Chuen Temple, Nong Ruea District, Khon Kaen Province. ‘7-Sor-Serm, 7-Dee’ were inserted in to the activities. Dhamma medicines that were inserted were the Three Puññakiriyāvatthu, including Dāna, Sīla, and Bhāvanā, and the Seven Sappāya Dhammas. 3. The model consisted of three models: the model of application of the Three Puññakiriyāvatthu, the application of the Seven Sappāya Dhammas, and the application of Thai traditional medicine for treating knee osteoarthritis patients. This leads to the model of application of Thai traditional medicine for treating knee osteoarthritis patients with Dhamma medicine according to Buddhist guidelines in Nong Ruea District, Khon Kaen Province. A new body of knowledge creates holistic well-being in four areas: physical, mental, intellectual, and social, resulting in sustainable happiness in all dimensions.